Spatial and Temporal Soil Moisture Variations over China from Simulations and Observations - Xin Lai; Jun Wen; Sixian Cen; Xi Huang; Hui Tian; Xiaokang Shi (Advances in Meteorology)
The Community Land Model version 4.0 (CLM4.0) driven by the forcing data of Princeton University was used to simulate soil moisture (SM) from 1961 to 2010 over China. The simulated SM was compared to the in situ SM measurements from International Soil Moisture Network over China, National Centers for Environmental Prediction (NCEP) Reanalysis data, a new microwave based multiple-satellite surface SM dataset (SM-MW), and European Centre for Medium-Range Weather Forecasts Interim Reanalysis (ERA Interim/Land) SM data. The results showed that CLM4.0 simulation is capable of capturing characteristics of the spatial and temporal variations of SM. The simulated, NCEP, SM-MW, and ERA Interim/Land SM products are reasonably consistent with each other; based on the simulated SM of summer, it can be concluded that the spatial distribution in every layer was characterized by a gradually increasing pattern from the northwest to southeast. The SM increased from surface layer to deeper layer in general. The variation trends basically showed consistencies at all depths. The simulated SM of summer demonstrated different responses to the precipitation variation. The variation distribution of SM and measured precipitation had consistencies. The humid region significantly responded to precipitation, while the semiarid and arid regions were ranked second.